95 years of the Malting Institute in Brno - Vratislav Psota (Kvasný průmysl, 2016)
The Malting Institute, currently the Brno’s workplace of the Research Institute of Brewing and Malting (further only RIBM), was founded on August 4, 1920. In 1933 a pilot experimental malthouse was put into operation in this Institute. The Institute organized Malting and Brewing Conventions, Moravian School of Malting in Brno and it published a journal Reports of the Institute of Fermentation Industry. In 1942–1945 it published Žila’s edition of brewing papers. In 1952 it became a part of the RIBM. Since 1993 employees of the Brno’s workplace of the RIBM have participated successfully in many tenders in the research area. The RIBM was privatized in 1994. Since 1998 the Barley Year Book has been published, this year book presents results obtained by the Brno’s workplace of the RIBM. In 2001, the RIBM became a certified workplace – the “Analytical Testing Laboratory – Malting Institute Brno”. The workplace closely cooperates with malt producers, barley breeders and universities.